Research of Reliability, Availability and Maintainability on the All-electronic Computer Interlocking System - He Tao; Ren Jianxin (Institute of Advanced Engineering and Science, 2014)
High levels of reliability and high security are the basic characteristics and requirements of railway signal systems. So, reliability, availability and maintainability (RAM) are necessarily analyzed before the computer interlocking system will be adopted. The All-electronic Computer Interlocking System, which is a new kind of interlocking system, still needs to analyze its RAM before being put to use. In this paper, the reliability methods and Markov model are adopted to analyze the RAM indexes of the All-electronic Computer Interlocking System when its execution layer equipped with the single configuration or the dual-redundant configuration, the paper also compares the indexes with that of the traditional computer-based interlocking system. Finally, the paper will briefly include suggestions on how the All-electronic Computer Interlocking System’s RAM indexes may be increased and also, how the system may be used practically.